(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Atherosclerosis is heart and blood vein diseases (STDs) and stroke main reason was large arteries inflammation disease. Here we are talking about an individual path and system point of view from the point of view atherosclerosis molecular, cellular, genetic and to the environment impact about current the concept seeing We are the last ones. to changes attention, we looked at them some unexpected biological laws brought released, atherosclerotic in lesions inflammation and smooth muscle of cells previously unknown heterogeneity, old age and clonal in hematopoiesis roles and intestine microflora with dependency these from the sentence.